Dietary fiber intake and risk of hormonal receptor-defined breast cancer in the European Prospective Investigation into Cancer and Nutrition study. - Ferrari, P; Rinaldi, S; Jenab, M; Lukanova, A; Olsen, A; Tjønneland, A; Overvad, K; Clavel-Chapelon, F; Fagherazzi, G; Touillaud, M; Kaaks, R; von Rüsten, A; et al. (2013)
BACKGROUND: Limited scientific evidence has characterized the association between dietary fiber intake and risk of breast cancer (BC) by menopausal status and hormone receptor expression in tumors. OBJECTIVE: We investigated the relation between total dietary fiber and its main food sources (vegetables, fruit, cereals, and legumes) and BC risk by using data from the European Prospective Investigation into Cancer and Nutrition (EPIC). DESIGN: A total of 11,576 invasive BC cases in 334,849 EPIC women mostly aged 35-70 y at baseline were identified over a median follow-up of 11.5 y. Dietary fiber was estimated from country-specific dietary questionnaires. Multivariable Cox proportional hazards regression models were used to quantify the association between dietary variables and BC risk with energy adjustment by using the residual method. Subgroup analyses were performed by menopausal status and estrogen receptor (ER) and progesterone receptor (PR) expression in tumors. RESULTS: BC risk was inversely associated with intakes of total dietary fiber [hazard ratio comparing fifth quintile to first quintile (HR(Q5-Q1)): 0.95; 95% CI: 0.89, 1.01; P-trend = 0.03] and fiber from vegetables (0.90; 0.84, 0.96; P-trend < 0.01) but not with fiber from fruit, cereals, or legumes. Overall, associations were homogeneous by menopausal status and ER and PR expression in tumors. For vegetable fiber, stronger associations were observed for estrogen receptor-negative and progesterone receptor-negative (HR(Q5-Q1):0.74; 95% CI: 0.59, 0.93; P-trend = 0.01) than for estrogen receptor-positive and progesterone receptor-positive tumors (0.92: 0.81, 1.03; P-trend = 0.05), with P-heterogeneity = 0.09. CONCLUSION: Diets rich in dietary fiber and, particularly, fiber from vegetables may be associated with a small reduction in risk of BC, independently of menopausal status.